Changing food consumption patterns: implications for nutrition and livelihoods - Halder, Shantana R; Urey, Ian (BRAC Research and Evaluation Division (RED), 2020)
This report presents a review results on the trends and patterns in food intake and nutritional status of the poor rural and urban households of Bangladesh during the period 1991-2000. It then looks at the socio-economic changes that have occurred during the last decade that have affected the food consumption pattern and the development of the food system. The 1990s was marked by a substantial increase in food production, however, the country is yet to achieve desired nutritional levels. The 1990s also saw substantial economic growth, with an associated decline in the incidence of both absolute poverty and extreme poverty. Parallel with food production and economic growth, poverty reduction, Bangladesh achieved notable reductions in child malnutrition rates during the nineties although percentage of malnourished children of the poor families was over 60%. Thus poor households, rural and urban alike, did not benefit proportionately from increased food production and the economic growth that the country achieved during the nineties. In 2000 the food intake of the poor was as low and imbalanced as it was in 1991. With the changes in food production and consumption, the total food system in Bangladesh is also changing. The growth of urban middle-income groups due to economic growth has created the demand for higher value products such as livestock products, fruits and vegetables. Increasing urbanisation and industrialisation has also encouraged market expansion for food products and increased market dependence for certain households. Transport infrastructure improved in the last decade. A more integrated food transportation network has developed which have increased the length of supply chains and the volume of food supplied. The integration of Bangladesh with the global economy expanded both the legal and illegal trade which have implications on the availability of food produce, dietary diversity, price stabilisation, and employment opportunities in the expanding sector.